2016
DOI: 10.1073/pnas.1600008113
|View full text |Cite
|
Sign up to set email alerts
|

SHAPE reveals transcript-wide interactions, complex structural domains, and protein interactions across the Xist lncRNA in living cells

Abstract: The 18-kb Xist long noncoding RNA (lncRNA) is essential for X-chromosome inactivation during female eutherian mammalian development. Global structural architecture, cell-induced conformational changes, and protein-RNA interactions within Xist are poorly understood. We used selective 2′-hydroxyl acylation analyzed by primer extension and mutational profiling (SHAPE-MaP) to examine these features of Xist at single-nucleotide resolution both in living cells and ex vivo. The Xist RNA forms complex welldefined se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
313
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(329 citation statements)
references
References 47 publications
15
313
0
1
Order By: Relevance
“…S3). Additionally, we successfully performed DO-RIP-seq experiments for HuR in mouse cells and identified many of the same sites in mouse as we observed in human (Smola et al 2016). While producing more HuR binding sites than reported in any other study, the locations and nucleic acid sequence characteristics were similar to previous observations (Levine et al 1993;Gao et al 1994;Ma et al 1996;Lebedeva et al 2011;Mukherjee et al 2011).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…S3). Additionally, we successfully performed DO-RIP-seq experiments for HuR in mouse cells and identified many of the same sites in mouse as we observed in human (Smola et al 2016). While producing more HuR binding sites than reported in any other study, the locations and nucleic acid sequence characteristics were similar to previous observations (Levine et al 1993;Gao et al 1994;Ma et al 1996;Lebedeva et al 2011;Mukherjee et al 2011).…”
Section: Resultssupporting
confidence: 81%
“…It is possible that some negative IP's may introduce biases such as the binding of aptameric RNAs to antibodies. However, we have found that our antibody-based approach to identify and quantify binding was complemented by nonantibody-based Delta-SHAPE experiments determining RBP binding sites in XIST lincRNA (Smola et al 2016). This suggests that antibody-based biases have a negligible effect on DO-RIP-seq binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation that these regions have higher sequence conservation suggests that interactions with the cellular environment may exert selective pressure on the RNA sequence. However, these differences do not occur with higher frequency in regions with low or high SHAPE reactivity (Supplemental Table 3), suggesting that interactions with the cellular environment are not limited to regions folding to single, well-defined conformations that have low median SHAPE (Smola et al 2016). …”
Section: ))mentioning
confidence: 99%
“…6B) conditions. This approach to visualizing the data enables us to identify regions of relatively high median SHAPE (less structure, more complex conformational ensemble) and relatively low median SHAPE (more structure, more likely a single conformation) (Smola et al 2016). We treated the protein:mRNA complex with 1M7 (bound), extracted RNA from cells, removing all proteins (unbound), or we transcribed RNA with T7 RNA polymerase and then treated with 1M7 (in vitro) (Supplemental Figs.…”
Section: Lackey 12mentioning
confidence: 99%
See 1 more Smart Citation